Germanizmy w polu ŚWIAT WOKÓŁ CZŁOWIEKA w brneńskim hantecu i gwarze miejskiej Poznania - Osowski, Błażej (Komisja Slawistyczna PAN, Oddział w Poznaniu, IFS UAM, Wydawnictwo PRO, 2016)
The article analyzes the semantic field around the world human and it’s individual subfields in the urban dialect of Brno and Poznan from germanism’s point of view. The analysis carried out in the context of a comparative reveal differences and common ground between the material and indicate their reasons for referring to the context of the historical-cultural-socially.
Keywords: urban dialect; Poznań; Brno; hantec; germanisms; semantic structure